Morphological Features of Bottle (Circular) Caries - Dzhuraevna, Khayitova Mokhinur (American Journal of Bioscience and Clinical Integrity, 2024)
Caries in early childhood (CVRV), formerly known as caries from a feeding bottle, caries from a baby bottle, caries from a night bottle and caries from a night bottle for feeding, is a disease affecting teeth in children aged from birth to 71 months. CVR is characterized by the presence of 1 or more affected (without carious cavities or with carious cavities), missing (due to caries) or filled tooth surfaces in any baby tooth. ECC has been shown to be a very common transmissible bacterial infection, usually transmitted from a primary caregiver to a child.